Rethinking Europe: Overcoming National Confines in Twentieth-Century Literature - Parry, Christoph (FRAME, Journal of Literary Studies, 2026)
This paper deals with the relationship between national and supranational literary contexts drawing on Pascale Casanova’s idea of a “World Republic of Letters” with its give and take between centre and periphery. James Joyce and Joseph Roth are then discussed as cosmopolitan authors who for different reasons moved out of their national contexts in the first half of the twentieth century. Finally, attention is turned to the impact of migrant writers on European literatures today and the challenge presented by enhanced global mobility to traditional conceptions of what comprises European cultural identity.